RFID Based Surveillance System for Preventing Tree Smuggling in Forest - Rai, Seema; Jeberson, Wilson (International Journal of Computer Sciences and Engineering, 2025)
From past few years we have been reading in the newspaper about cutting and smuggling of precious trees, these trees are very costly as well as important in the world, trees are used in medical science as well as cosmetic because of huge amount of money is involved in selling of such tree woods, lots of incidents are happening of cutting of trees and their smuggling.. To protect such type of smuggling protecting system need to be developed. In proposed system, In order to detect cutting down of valuable trees immediately we use vibration sensor and continuity sensor, here vibration sensor is used to sense the vibration created during cutting down the trees and continuity sensor check the connectivity between neighbouring trees, buzzer along with RFID and bluetooth is used. When smuggler start cutting the tree, the vibration level of the tree is increased is sensed by vibration sensor then it immediately send alert buzzer to control unit. If the smuggler remove the tag then cut the tree the continuity between the neighbouring trees will be break then also it send alert buzzer to control unit and immediate action can be taken